Developing The Snake And Ladder Game As Media For Teaching Vocabulary At Ma Al Khoiriyah - Latifah, Nurriatul; Saifuddin, Ahmad; Widiarini, Widiarini (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to develop snakes and ladders game as learning media to teach descriptive text vocabulary at X class students of MA Al Khoiriyah Putukrejo Gondanglegi Malang. The research method used was the research and development (R&D) method with the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The population of this study were 20 students at X class of MA Al Khoiriyah and the sample was taken by using cluster random sampling method. The instruments used in data collection were questionnaires and unstructured interviews. The results showed that the snakes and ladders learning media for descriptive text vocabulary was very valid and effective in increasing students' learning motivation. In this learning media, students are not only asked to answer questions in each box of snakes and ladders boards, but also to make sentences related to the vocabulary that has been translated. After the game was over, students must remember the new vocabulary that has been found and recorded on the blackboard by the teacher. This research is expected to make a positive contribution in the development of effective and innovative learning media to increase student learning motivation.